What Is a Good Workplace? Tracing the Logics of NPM among Managers and Professionals in Swedish Elderly Care - Keisu, Britt-Inger; Öhman, Ann; Enberg, Birgit (Nordic Journal of Working Life Studies, 2016)
Neoliberal policies such as new public management (NPM) have been pivotal to the Swedish elderly care system for two decades. This article explores the discourses of NPM and work by focusing on how a good workplace is represented by professionals and managers in Swedish elderly care. Using qualitative interviews with 31 managers, nurses, physiotherapists, and occupational therapists at nine workplaces, we identified four competing meanings (‘storylines’) of how a good workplace is constructed among the interviewees within an ongoing struggle between two discourses. Three storylines, i.e., striving to achieve the mission, a desire to work in elderly care, and striving for good working relationships, are linked to the neoliberal discourse of organizational effectiveness. In contrast, the fourth storyline, support and better working conditions, is related to a welfare-state discourse of traditional labor relations with strong historical roots. Four subject positions available to the managers and professionals were identified: the bureaucrat, the passionate, the professional, and the critic. We conclude that NPM is translated on top of existing discourses, such as those of traditional labor relations, care ideals, and practices, that are already established in elderly care workplaces and that counteract the new policy.